Current Controversies in Newer Therapies to Treat Birth Asphyxia - Wintermark, Pia (Hindawi Publishing Corporation, 2011)
Despite major advances in monitoring technology and knowledge of fetal and neonatal pathophysiology, neonatal hypoxic-ischemic encephalopathy (HIE) remains one of the main causes of severe adverse neurological outcome in children. Until recently, there were no therapies other than supportive measures. Over the past several years, mild hypothermia has been proven to be safe to treat HIE. Unfortunately, this neuroprotective strategy seems efficient in preventing brain injury in some asphyxiated newborns, but not in all of them. Thus, there is increasing interest to rapidly understand how to refine hypothermia therapy and add neuroprotective or neurorestorative strategies. Several promising newer treatments to treat birth asphyxia and prevent its devastating neurological consequences are currently being tested. In this paper, the physiopathology behind HIE, the currently available treatment, the potential alternatives, and the next steps before implementation of these other treatments are reviewed.